1996
DOI: 10.1016/0375-9474(96)00231-x
|View full text |Cite
|
Sign up to set email alerts
|

Meson loops in the Nambu-Jona-Lasinio model

Abstract: The effects of meson loops in the vacuum sector of the Nambu-Jona-Lasinio model are calculated. Using the effective action formalism we take consistently all nextto-leading-order 1 Nc terms into account. This leads to a symmetry-conserving approach, in which all features of spontaneously broken chiral symmetry, such as the Goldstone theorem, the Goldberger-Treiman and the Gell-Mann-Oakes-Renner relations are preserved. Contributions to qq and F π are calculated, and are shown to be substantial, at the level of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
127
1

Year Published

1996
1996
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 66 publications
(134 citation statements)
references
References 30 publications
6
127
1
Order By: Relevance
“…The situation is more complicated in a nonlocal than a local model [6,8] because there are two kinds of contribution to be considered, arising from the local and nonlocal parts of the symmetry current (see Sec. II).…”
Section: Meson Coupling To a Currentmentioning
confidence: 99%
See 2 more Smart Citations
“…The situation is more complicated in a nonlocal than a local model [6,8] because there are two kinds of contribution to be considered, arising from the local and nonlocal parts of the symmetry current (see Sec. II).…”
Section: Meson Coupling To a Currentmentioning
confidence: 99%
“…Even if the calculations were of interest for no other reason, a check on this perturbative approach would be very valuable. Encouragingly, there seems to be a general consensus emerging from recent studies that NLO corrections are indeed relatively small for standard choices of the model parameters [6,8,[10][11][12][13][14][15], at least for properties of the ground state and of the pion. A contrary view, however, has been expressed by Kleinert and Van den Bossche [16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other authors have investigated NTL effects in NJL-type frameworks without gauge bosons [28], [35]- [38]. The authors of [28] calculated the NTL effects with an effective action formalism, and those of [35] with diagrammatic methods.…”
Section: Conclusion and Comparison To Other Workmentioning
confidence: 99%
“…Only a few studies that go beyond the mean field approximation were reported. Nikolov et al [17] extended the mean field approximation to the next-to-leading order in 1/N that includes the meson loop contributions. The extension preserves the symmetry property of the theory.…”
mentioning
confidence: 99%